Pool boiling of Novec 7300 and DI water on nano-textured heater covered with supersonically-blown or electrospun polymer nanofibers. (March 2017) - Sinha-Ray, Sumit; Zhang, Wenshuo; Sahu, Rakesh P.; Sinha-Ray, Suman; Yarin, Alexander L.
Graphical Abstract: Highlights: Pool boiling of two fluids was studied on bare and nanofiber-coated surface. Supersonically-blown ultrafine nanofibers provide large number of nucleation sites. Ultrafine nanofibers outperformed bare or electrospun nanofiber-coated surfaces. Such nanofibers are robust and they do not delaminate after prolonged boiling. Abstract: In this work we study pool boiling of Novec 7300 and DI water on bare copper surface and copper surface covered with supersonically-blown or electrospun polymer nanofibers. In distinction from the previous works nanofibers were not metal-plated. The elimination of the electroplating makes nano-texturing process extremely simple and applicable to a wide variety of surfaces. On the other hand, it comes with the price of a lower heat removal rate compared to that on metal-plated nanofibers, albeit the present experiments revealed that the reduction is not that drastic as it would be expected. It is also demonstrated that the supersonically-blown polymer nanofibers also outperformed the electrospun nanofiber-coated surface. Supersonically-blown nanofibers provide a larger number of nucleation sites than electrospun nanofibers or bare copper surface, and thus, facilitate nucleate boiling much stronger. The ultrafine supersonically-blown polymer nanofibers are very robust and did not delaminate from the heater surface either in Novec 7300 or DI water after prolonged vigorous boiling process. Overall, the enhancement of heat removal due to the ultrafine supersonically-blown polymer nanofibers on the heater surface in Novec 7300 is more significant than in DI water, which is associated with the smaller bubble size in the former case.